A novel splice variant of Elp3/Kat9 regulates mitochondrial tRNA modification and function - Boutoual, Rachid; Jo, Hyunsun; Heckenbach, Indra; Tiwari, Ritesh; Kasler, Herbert; Lerner, Chad A.; Shah, Samah; Schilling, Birgit; Calvanese, Vincenzo; Rardin, Matthew J.; Scheibye-Knudsen, Morten; Verdin, Eric (Scientific reports, 2022)
Post-translational modifications, such as lysine acetylation, regulate the activity of diverse proteins across many cellular compartments. Protein deacetylation in mitochondria is catalyzed by the enzymatic activity of the NAD + -dependent deacetylase sirtuin 3 (SIRT3), however it remains unclear whether corresponding mitochondrial acetyltransferases exist. We used a bioinformatics approach to search for mitochondrial proteins with an acetyltransferase catalytic domain, and identified a novel splice variant of ELP3 (mt-ELP3) of the elongator complex, which localizes to the mitochondrial matrix in mammalian cells. Unexpectedly, mt-ELP3 does not mediate mitochondrial protein acetylation but instead induces a post-transcriptional modification of mitochondrial-transfer RNAs (mt-tRNAs). Overexpression of mt-ELP3 leads to the protection of mt-tRNAs against the tRNA-specific RNase angiogenin, increases mitochondrial translation, and furthermore increases expression of OXPHOS complexes. This study thus identifies mt-ELP3 as a non-canonical mt-tRNA modifying enzyme.